The Ethnolinguistic Values of Madura Ca’ocaan as a Foundation of Indigenous Character Development for Counselors / Nilai Etnolinguistik Ca’ocaan Madura sebagai Fondasi Indigenous Character Development bagi Konselor - Arinal Haq Fauziah; Ishlakhatus Sa’idah; Amaliah Aryani; Akmalul Umam; Jenius Dwi Pangestu (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2026)
Language, as a cultural product, not only reflects collective identity but also serves as a medium for the transmission of social values within a society. One form of oral cultural expression among the Madurese people is Ca’ocaan, which contains moral messages, communication ethics and social norms. This study aims to examine the ethnolinguistic meaning of Madurese Ca’ocaan and analyse its relevance as a foundation for the development of counsellor character. This study employs a qualitative approach using a communication ethnography (ethnography of speaking) design, which focuses on the interpretation of language practices within the socio-cultural context of the community. Data were collected through participant observation and in-depth interviews regarding the practice of Ca’ocaan in the Sampang region of Madura. Data analysis was conducted thematically by interpreting the meaning of utterances based on cultural context, speech situations, and local community interaction norms. The research findings indicate that Ca’ocaan expressions, such as “Mon e delem pol-ngompol, jhek kenceng akalengka ka oreng ben jhek kenceng alon-callon mon bereng tak duggeh”, embody values of politeness, self-control, empathy, and social sensitivity, which align with the core competencies of counsellors in the humanistic approach. These findings confirm that Ca’ocaan has the potential to serve as an ethical and pedagogical resource in counselling education based on local culture.